2001
DOI: 10.1007/s004680100110
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hydraulic resistance and leaf morphology in broadleaf Quercus species: a new interpretation of leaf lobation

Abstract: We investigated the relationship between leaf shape and leaf hydraulic resistance in a set of broadleaf Quercus tree species (Q. cerris, Q. frainetto, Q. petraea, Q. pyrenaica, Q. robur, Q. rubra, Q. velutina). Seedlings of all the studied species were grown under uniform environmental conditions. A new high-pressure flowmeter was designed to measure leaf-blade hydraulic resistance. Leaf shape was characterised by the complexity of leaf outline which was regarded as an estimate of leaf lobation. This was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 23 publications
3
51
1
3
Order By: Relevance
“…Similar results have been found for Quercus in response to different levels of ambient light and to nutritional stress (Balaguer et al, 2001;Valladares et al, 2000). Sisó et al (2001) have shown that leaf hydraulic resistance was negatively related to ILB in broadleaf Quercus species, suggesting that the lower hydraulic resistance in deeply lobed leaves may constitute a mechanism for improving water balance under dry atmospheric conditions.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results have been found for Quercus in response to different levels of ambient light and to nutritional stress (Balaguer et al, 2001;Valladares et al, 2000). Sisó et al (2001) have shown that leaf hydraulic resistance was negatively related to ILB in broadleaf Quercus species, suggesting that the lower hydraulic resistance in deeply lobed leaves may constitute a mechanism for improving water balance under dry atmospheric conditions.…”
Section: Discussionsupporting
confidence: 79%
“…In this experiment, the effects of light and temperature were not decoupled and warrant further investigation. Lobed leaves may also reduce self-shading, increase interception of horizontally projected light, or help plants cope with moisture stress (Rich et al 1995;Sisó et al 2001). Conversely, leaf lobing could be a selectively neutral trait that evolved under past climates (McGlone & Webb 1981).…”
Section: Discussionmentioning
confidence: 99%
“…resistencia al flujo) de las partes aéreas de la planta, como uno de los requerimientos básicos que han garantizado la colonización de los ambientes terrestres por parte del mundo vegetal (Gil-Pelegrín 1993). Mientras que la humedad edáfica, o su equivalente energético, ha sido objeto de una extrema atención por parte de los fisiólogos vegetales (en especial por aqué-llos vinculados al universo de las plantas cultivadas) se ha prestado mucha menos atención al potencial hídrico atmosférico (Sisó et al 2001b), pudiendo ser un pará-metro que defina la transición de los paisajes típica-mente templados (sin sequía edáfica o atmosférica) a los genuínamente mediterráneos (con sequía edáfica y atmosférica). Los paisajes de transición podrían responder a situaciones donde la disponibilidad de agua en el suelo es alta pero donde se desarrollan elevados gradientes de potencial entre la hoja y el aire.…”
Section: El Continuo Suelo-planta-atmósfera Como Un Modelo Integradorunclassified
“…Los paisajes de transición podrían responder a situaciones donde la disponibilidad de agua en el suelo es alta pero donde se desarrollan elevados gradientes de potencial entre la hoja y el aire. En estas condiciones, los «derrochadores de agua», en el sentido que les da Levitt (1972), podrían ser adecuados como alternativa a los «ahorradores» estrictos (Sisó et al 2001b, Vilagrosa et al 2003b). …”
Section: El Continuo Suelo-planta-atmósfera Como Un Modelo Integradorunclassified
See 1 more Smart Citation